Status of woodland caribou in Alberta - Edmonds, J. (Rangifer, 1998)
A recent review of woodland caribou Rangifer tarandus caribou) status in Alberta estimated that there are between 3600 and 6700 caribou occupying 113 000 km2 of habitat. There are two ecotypes of caribou in Alberta; the mountain ecotype in the west central region and the boreal ecotype primarily in the north. Mountain caribou populations are stable or declining and boreal populations, where data are available, appear to be stable or declining slowly. A major initiative in caribou management in Alberta has been the development of the Woodland Caribou Conservation Strategy. This document was developed over two and a half years by a committee of multi-stakeholder representatives. The past five years has seen an increase in baseline inventory and applied research jointly funded by government, industry and universities, addressing a wide range of management issues from caribou response to logging to interactions of moose, wolves and caribou in the boreal ecosystem. Land use conflicts on caribou range remain high with timber harvesting, oil and gas development, peat moss extraction, coal mining, agricultural expansion and increasing road access overlapping. Cumulative effects of these disturbances are poorly understood and have received little attention to date.